2015
DOI: 10.1007/s00484-015-1054-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermal comfort in Quebec City, Canada: sensitivity analysis of the UTCI and other popular thermal comfort indices in a mid-latitude continental city

Abstract: The newly developed Universal Thermal Climate Index (UTCI), along with the physiological equivalent temperature (PET), the humidex (HX) and the wind chill index (WC), was calculated in Quebec City, Canada, a city with a strong seasonal climatic variability, over a 1-year period. The objective of this study is twofold: evaluate the operational benefits of implementing the UTCI for a climate monitoring program of public comfort and health awareness as opposed to relying on traditional and simple indices, and det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
21
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 40 publications
6
21
0
2
Order By: Relevance
“…Only the UTCI index fluctuates considerably under T a Class1 and Class2 conditions, having the highest sensitivity among the selected indices. The above findings are in agreement with the results of Charalampopoulos [27] and Provençal et al [106] which confirm the low sensitivity to WS and the comparatively higher sensitivity of UTCI. Additionally, it was found that as T a increases, the UTCI sensitivity lowered, and under hot conditions (Class 4, 30 • C < T a ≤ 45 • C) the UTCI presented lower mean sensitivity in comparison to the cases of PET's and mPET's.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Only the UTCI index fluctuates considerably under T a Class1 and Class2 conditions, having the highest sensitivity among the selected indices. The above findings are in agreement with the results of Charalampopoulos [27] and Provençal et al [106] which confirm the low sensitivity to WS and the comparatively higher sensitivity of UTCI. Additionally, it was found that as T a increases, the UTCI sensitivity lowered, and under hot conditions (Class 4, 30 • C < T a ≤ 45 • C) the UTCI presented lower mean sensitivity in comparison to the cases of PET's and mPET's.…”
Section: Discussionsupporting
confidence: 92%
“…The gradient of the sensitivity patterns accompanied by the summary statistics proves that VP has a weak influence on 'G' category indices' fluctuation. This finding is in agreement with the results of [27], but when examining the comparative indices' sensitivity, those results are partially in contrary with the results of [106] since they found that the UTCI is less sensitive than PET and mPET. According to analysis undertaken by this study, the UTCI is more sensitive than PET and mPET under lower VP environments, but less so for conditions with high VP values.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations